Comparison of Light Transmission Aggregometry With Impedance Aggregometry in Patients on Potent P2Y12 Inhibitors. (May 2021) - Wadowski, Patricia P.; Pultar, Joseph; Weikert, Constantin; Eichelberger, Beate; Lang, Irene M.; Koppensteiner, Renate; Panzer, Simon; Gremmel, Thomas
Since data on the agreement between light transmission aggregometry (LTA) and multiple electrode aggregometry (MEA) in patients on the more potent P2Y12 inhibitors are missing so far, we investigated if the evaluation of the responsiveness to therapy by LTA can be replaced by MEA in 160 acute coronary syndrome (ACS) patients on dual antiplatelet therapy with aspirin and prasugrel or ticagrelor (n = 80 each). Cut-off values for high on-treatment residual platelet reactivity (HRPR) in response to adenosine diphosphate (ADP) or arachidonic acid (AA) were defined according to previous studies showing an association of HRPR with the occurrence of adverse ischemic outcomes. ADP- inducible platelet aggregation was 33% and 37% ( P = 0.07) by LTA and 19 AU and 20 AU ( P = 0.38) by MEA in prasugrel- and ticagrelor-treated patients, respectively. AA- inducible platelet aggregation was 2% and 3% by LTA and 15 AU and 16 AU by MEA, (all P ≥ 0.3) in patients on prasugrel and ticagrelor, respectively. By LTA, HRPR ADP and HRPR AA were seen in 5%/5% and in 4%/ 13% of patients receiving prasugrel- and ticagrelor, respectively. By MEA, HRPR ADP and HRPR AA were seen in 3%/ 25% and 0%/24% of prasugrel- and ticagrelor-treated patients, respectively. ADP-inducible platelet reactivity by MEA correlated significantly with LTA ADP in prasugrel-treated patients (r = 0.4, P < 0.001), but not in those receiving ticagrelor (r = 0.09, P = 0.45). AA-inducible platelet aggregation by LTA and MEA did not correlate in prasugrel- and ticagrelor-treated patients. Sensitivity/specificity of HRPR by MEA to detect HRPR by LTA were 25%/99% for MEA ADP and 100%/79% for MEA AA in prasugrel-treated patients, and 0%/100% for MEA ADP and 70%/83% for MEA AA in ticagrelor-treated patients. In conclusion, on-treatment residual ADP-inducible platelet reactivity by LTA and MEA shows a significant correlation in prasugrel- but not ticagrelor-treated patients. However, in both groups LTA and MEA revealed heterogeneous results regarding the classification of patients as responders or non-responders to P2Y12 inhibition.